2019
DOI: 10.1016/j.nmni.2019.100525
|View full text |Cite
|
Sign up to set email alerts
|

Demodicosis revealing an HIV infection

Abstract: We report an observation of facial and upper limb demodicosis, revealing a human immunodeficiency virus infection. After an initial improvement with metronidazole, worsening of skin lesions related to immune reconstitution inflammatory syndrome was observed, requiring the use of steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…According to the literature data, immunosuppression is an important predisposing factor for development of symptomatic Demodex spp. invasion [ 31 , 32 , 33 , 34 ]. On the other hand, the research conducted by Kosik-Bogacka in the group of patients with haematologic diseases did not show any significant differences between the prevalence of D. folliculorum in the study group and in the control group [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature data, immunosuppression is an important predisposing factor for development of symptomatic Demodex spp. invasion [ 31 , 32 , 33 , 34 ]. On the other hand, the research conducted by Kosik-Bogacka in the group of patients with haematologic diseases did not show any significant differences between the prevalence of D. folliculorum in the study group and in the control group [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar immunopathogenesis in these disease groups may also be responsible for the association of facial dermatoses and blepharitis. The presence of STAT-1 gene mutations that cause a primary immunodeficiency, which is blamed especially in the etiology of rosacea, Demodicosis, blepharitis, or the emergence of Demodicosis, SD and rosacea in secondary immunodeficiency cases may be a consociate etiopathogenetic factor [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 115 cases of demodicosis reported three cases related to immunodeficiencies (20). Demodicosis in patients with human immunodeficiency virus infection (21)(22)(23)(24), with an immune reconstitution inflammatory syndrome (25)(26)(27)(28), or in a patient with ataxia-telangiectasia ( 29) has been reported. The impaired IL-17-mediated immunity, with low Th17 cell proportions, in STAT1 GOF patients may explain the proliferation of Demodex (30), leading to the occurrence of demodicosis, especially rosacea-like demodicosis (31).…”
Section: Discussionmentioning
confidence: 99%